2020
DOI: 10.1371/journal.pone.0227880
|View full text |Cite
|
Sign up to set email alerts
|

Paired walkers with better first impression synchronize better

Abstract: This study measured automatic walking synchronization and how it associates with social impression. Previous studies discovered positive social consequence of motor synchrony with ecological paradigms (e.g. body movement synchrony between therapists and patients in clinical sessions, and the synchrony of side-by-side walkers). However, most studies of joint movement with high ecological validity face the same challenge, namely that conversations between participants might be the main or a partial contributor t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…It is known that people's movement while walking influences one another [28]. For example, when two people are walking, the mutual first impressions change the degree of entrainment of each individual's gait [29]. Using this mobile robot platform, in the future, we will investigate how the motion of CoM, that is, an additional degree of freedom, influences human-robot interaction [30].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that people's movement while walking influences one another [28]. For example, when two people are walking, the mutual first impressions change the degree of entrainment of each individual's gait [29]. Using this mobile robot platform, in the future, we will investigate how the motion of CoM, that is, an additional degree of freedom, influences human-robot interaction [30].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that factors related to affiliation influences synchrony and vice versa. For example, people who do not like each other tend to be less in sync [ 106 , 163 ] than people who like each other [ 108 , 121 ]. Research also show increases in variables related to affect and affiliation between adults following a nonspontaneous synchronization, positive affect [ 30 ], social bonding [ 35 ], and trust [ 109 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, experimental studies elicit synchrony in adults through joint tasks that require intentional or unintentional synchronization in time and form with a referent (e.g., a metronome, a pre-recorded video, or another adult participant). Examples of such joint tasks include finger tapping [107,115], rocking in a rocking chair [116,117], swinging pendulums [118][119][120], climbing stairs [106], walking [121][122][123][124] or jumping [125].…”
Section: The Present Studymentioning
confidence: 99%
“…A first set of studies investigated rhythmic activities, such as walking (Cheng et al, 2017(Cheng et al, , 2020, rocking chairs (Demos et al, 2012), finger flexion (Nordham et al, 2018), "body conversation" (Galbusera et al, 2019), or required participants to stay near each other without any conversation or a common goal (Varlet et al, 2011.…”
Section: Rhythmic Activities and Body Swaymentioning
confidence: 99%
“…A first set of studies used the terminology interpersonal coordination referring to "dynamical process of self-organization, " "spatiotemporal organization of movement, " or "dynamical entrainment" (Varlet et al, 2011Demos et al, 2012;Fujiwara et al, 2016;Paxton and Dale, 2017;Nordham et al, 2018;Fujiwara et al, 2019;Wiltshire et al, 2019). On the other hand, others used the terminology synchrony, referring to "variables of a system becoming entrained" or as "specious present, " and "smooth meshing in time of the simultaneous rhythmic activity" or "the coordinated overall body movement" of two interacting individuals (Schmidt et al, 2012;Tschacher et al, 2014Tschacher et al, , 2018Abney et al, 2015;Cheng et al, 2017Cheng et al, , 2020Lozza et al, 2018;Galbusera et al, 2019;Sun et al, 2019). Finally, Hale et al (2020) referred to mimicry and complementary behavior.…”
Section: Jingle-jangle Fallacymentioning
confidence: 99%